Game Edukasi “Kids Learning” Sebagai Media Pembelajaran Dasar Untuk Anak Usia Dini Berbasis Android - Wanty Eka Jayanti; Eva Meilinda; Nana Fahriza (Universitas Bina Sarana Informatika, 2018)
Technology is one of today's lifestyles. With android, humans can get entertainment without having to go to a place, one of them through the game contained on android. Can not be denied many interesting and exciting game options to be played everyday at this time, but unfortunately the material contained in the game is more only intended for entertainment and minimum value is useful. For that reason researchers took the initiative to make the game